Shock Initiation by Shear Band Formation - Partom, Yehuda (European Journal of Applied Sciences, 2022)
Shock initiation of explosives usually comes about by hot spot formation through void collapse. But very weak shocks, under the hot spot formation threshold, can still lead to shock initiation through the process of shear band formation. We performed weak shock tests in the so-called explosive-window configuration, to determine the shear initiation threshold of the explosive PBX9501. We then ran computer simulations with our shear initiation model, and were able to reproduce a reasonable approximation to the test results.